Hospitality Student’s Perception of English Online Learning During the Covid 19 Pandemic - Supartini, Ni Luh; Sri Rahayu, Ni Made (International Seminar on Austronesian Languages and Literature, 2021)
Covid - 19 Pandemic rapidly spread across the globe, and it affects many sectors in the world including education system. Before, the process of teaching and learning can be done through direct meeting, however it has changed into online learning. This issue becomes a challenge to hospitality school in which the students required to have 60% practice rather than theory. The teacher should be able transfer the practice class into online learning. This study discussed students’ responses for online learning in hospitality school during this pandemic. Data were collected through questionnaire created on Google form consisting of 20 questions. The number of research respondent was 90 students of hospitality department from different semester at International Institute of Tourism and Business. The result showed that internet connection was the main problems in online learning. However, students enjoyed the learning process by providing some online activities at the of meetings